PEMBATASAN TERHADAP HAK ASASI MANUSIA DALAM PRESPEKTIF KEADAAN DARURAT - Matompo, Osgar S (Jurnal Media Hukum, 2014)
HumanÂ  rightsÂ  is a giftÂ  from Allah SWT, as a consequence becoming humanÂ  creature, thereforeÂ  it couldnât be deprivedÂ  orÂ  abolishedÂ  byÂ  theÂ  state.Â  IfÂ  aÂ  stateÂ  inÂ  anÂ  abnormalÂ  conditionÂ  orÂ  emergencyÂ  condition,Â  stateÂ  is allowedÂ  toÂ  take an extraordinary actionÂ  including giving restrictionÂ  to humanÂ  rightÂ  forÂ  theÂ  sake of defending stateÂ  integrityÂ  andÂ  protectÂ  itsÂ  citizens, butÂ  humanÂ  rightÂ  thatÂ  couldÂ  beÂ  restrictedÂ  isÂ  humanÂ  right whichÂ  is categorizedÂ  inÂ  non-derogableÂ  rightÂ  (rightÂ  thatÂ  couldnâtÂ  beÂ  limitedÂ  inÂ  anyÂ  kind ofÂ  condition).Â  ThisÂ  research foundÂ  thatÂ  inÂ  the practice of humanÂ  right restriction whichÂ  is appliedÂ  in any kind of emergency conditionÂ  in various area ofÂ  Indonesia preciselyÂ  touchÂ  theÂ  rights which are non-derogableÂ  rights.